Features of the European Union countries digitalization in the conditions of globalization - Samoilenko, Alla (Herald of Economics, 2021)
Introduction. Developed countries began to digitize their national economies resulting in transformation of human capital with digital and information technologies by making new demands on education. Transformational changes in the conditions of the world society development in the context of globalization put forward the need to reform the system of training, retraining and advanced training, as well as to promote the development of human capital creative abilities in accordance with the needs of the digital economy.The purpose of the study is to provide a scientific bases for the definition of the «digital economy» concept and to distinguish its key components, to outline the digitalization features and identify «digital gaps» in the EU countries using the Index of Digital Economy and Society (DESI).Methods. According to the purpose of the study, modern scientific methods of cognition were used, in particular: general scientific research methods (logical analysis, theoretical grounding, ascent from abstract to concrete, formalization and generalization), as well as the method of statistical observation.Results. The article presents the author’s views on the interpretation of the “digital economy” concept which allowed detailing the individual properties and structural elements of the digital economy. Based on the research by the Organization for Economic Co- operation and Development (OECD), three main components of the digital economy are presented. The infrastructure of the digital economy is identified with market and planning approaches. Using the DESI Index on the example of EU countries, an analysis of five key components was performed, including communications, human capital, the Internet use, integration of digital technologies and digital public services. The current state of digital economy in the EU countries was also presented. The author emphasizes the importance of governments role and their prudent policy to motivate the population to use digital and information technologies, to increase awareness in this area and the overall level of country digitalization.Discussion. The success of the country in the digital economy development will further depend on the national digital and information capabilities, the development of internal infrastructure, the readiness of society for transformational changes, dictated by globalization. The necessary legal framework of the digital economy, balanced state strategies for IT development, formation of the potential for professional skills development and basic ICT literacy, as well as professional career in the information field will result in positive changes in national economies under context of digitalization.Perspectives. Prospects for further research include the need for statistical analysis of the digital economy key components in the regional context of the world countries, actions ranking and sequencing in the theoretical and methodological support of measures to enhance the use of digital and information products by countries.